IN SITU HYBRID SPACES AS GENERATIVE SITES FOR TEACHER PREPARATION - Schnellert, Leyton; Kozak, Donna (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2019)
In this study, a university professor and school district literacy coordinator co-designed and co-taught a literacy methods course where teacher candidates participated in dynamic learning in classrooms, exploring how theory can meet practice when students’ funds of knowledge are valued through responsive teaching. Case study methodology was taken up to understand and enhance this in situ teacher education approach. Four themes were derived through qualitative analysis: 1) theory / practice connections in situ; 2) diverse learners and the need for responsivity in teaching; 3) in situ learning through collaboration; and 4) benefits and tensions at the school and program level. Findings suggest that school / university in situ teacher education partnerships can provide rich contextual and situational learning that disrupt normative conceptions of teaching, learning and literacy.